Complete Genome Sequence of the Genetically Tractable Hydrogenotrophic Methanogen Methanococcus maripaludis - Erik L. Hendrickson; Rajinder Kaul; Yang Zhou; Donald Bovee; Peter D. Chapman; J. Chung; Everly Conway de Macario; Jeremy A. Dodsworth; Will Gillett; David E. Graham; Murray Hackett; Andrew Haydock; et al. (2004)
The genome sequence of the genetically tractable, mesophilic, hydrogenotrophic methanogen Methanococcus maripaludis contains 1,722 protein-coding genes in a single circular chromosome of 1,661,137 bp. Of the protein-coding genes (open reading frames [ORFs]), 44% were assigned a function, 48% were conserved but had unknown or uncertain functions, and 7.5% (129 ORFs) were unique to M. maripaludis. Of the unique ORFs, 27 were confirmed to encode proteins by the mass spectrometric identification of unique peptides. Genes for most known functions and pathways were identified. For example, a full complement of hydrogenases and methanogenesis enzymes was identified, including eight selenocysteine-containing proteins, with each being paralogous to a cysteine-containing counterpart. At least 59 proteins were predicted to contain iron-sulfur centers, including ferredoxins, polyferredoxins, and subunits of enzymes with various redox functions. Unusual features included the absence of a Cdc6 homolog, implying a variation in replication initiation, and the presence of a bacterial-like RNase HI as well as an RNase HII typical of the Archaea. The presence of alanine dehydrogenase and alanine racemase, which are uniquely present among the Archaea, explained the ability of the organism to use L- and D-alanine as nitrogen sources. Features that contrasted with the related organism Methanocaldococcus jannaschii included the absence of inteins, even though close homologs of most intein-containing proteins were encoded. Although two-thirds of the ORFs had their highest Blastp hits in Methanocaldococcus jannaschii, lateral gene transfer or gene loss has apparently resulted in genes, which are often clustered, with top Blastp hits in more distantly related groups.